1984
DOI: 10.1161/01.hyp.6.5.724
|View full text |Cite
|
Sign up to set email alerts
|

Red cell cotransport activity and sodium content in black men. Relationship to essential hypertension.

Abstract: SUMMARY Furosemide-sensitive sodium and potassium cotransport and intracellular sodium content ([Na],) were measured in erythrocytes (red blood cells, RBCs) from a population of 90 adult black men with and without essential hypertension (EH). The mean values for sodium cotransport activity, expressed as furosemide-sensitive Na efflux (mmol/liter RBC/hr), were not significantly different among the EH patients and two control groups, normotensive subjects with a positive history (N + ) and those with a negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Nevertheless, in a previous report we described a small but significant [Na], elevation (9.66 ±3.02 vs 7.96 ±1.97 mmol/L RBC) in subjects with EH as compared with NT controls. 13 However, all the EH subjects had been treated with antihypertensive medications and had been withdrawn from therapy 2 to 6 weeks before entering the study. Therefore, these subjects were more similar to the currently described PEH subjects, who had significantly higher RBC [Na], levels than their NT controls (10.27 ± 3.23 vs 7.97 ± 2.16 mmol/L RBC; p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in a previous report we described a small but significant [Na], elevation (9.66 ±3.02 vs 7.96 ±1.97 mmol/L RBC) in subjects with EH as compared with NT controls. 13 However, all the EH subjects had been treated with antihypertensive medications and had been withdrawn from therapy 2 to 6 weeks before entering the study. Therefore, these subjects were more similar to the currently described PEH subjects, who had significantly higher RBC [Na], levels than their NT controls (10.27 ± 3.23 vs 7.97 ± 2.16 mmol/L RBC; p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…However, outward K cotransport did not differ between study groups. Ringel et al 23 also found no difference in RBC Na + -K + outward cotransport between normotensive and hypertensive black men, noting that cotransport was not different between normotensive black men with and without a family history of hypertension. We previously reported lower mean levels of RBC outward Na + -K + cotransport in black normotensive and hypertensive subjects as compared with whites and no effect of family history of hypertension on cotransport function in blacks.…”
Section: Intracellular Cation Concentrationmentioning
confidence: 94%
“…A high K m value for Naj activation of outward Na + -K + cotransport has been reported in young blacks with salt-sensitive hypertension. 23 Thus, a major difference in RBC cotransport between blacks and whites appears to be a reduced affinity of Naj for its internal cotransport binding site in black subjects. In some blacks the high K 05 was accompanied by low V,^ values, but in others Vr eached normal levels.…”
Section: Intracellular Cation Concentrationmentioning
confidence: 99%
“…Indeed, these authors were unable to detect any abnormality in the erythrocyte Na + contents of American hypertensive patients. 2 In conclusion, the extensive investigation of Na + transport systems in erythrocytes from essential hypertensive patients supports the idea that none of the red blood cell abnormalities (and even less the "increased red cell Na + content") is a common denominator of primary hypertension. Conversely, it appears that "essential hypertension" is a common denominator of very different diseases at the molecular level.…”
mentioning
confidence: 61%